MEASURING ALIGNMENT BETWEEN SINGLE NATIONAL CURRICULUM ENGLISH 2020 STANDARDS AND PUNJAB EXAMINATION COMMISSION ASSESSMENT 2023-2024 (Contemporary Journal of Social Science Review, 2025)
Alignment ensures standardization among curriculum standards, instruction, and assessment to meet the diverse needs of learners. The current study was structured to explore the alignment between the Single National Curriculum (SNC) 2020 English and the Punjab Examination Commission (PEC) assessment for the 8th-grade 2023-2024. The current study was a quantitative content analysis, using the online Webb’s Alignment Tool Second Version (WAT V2). The sources of data were SNC English, the textbook, PEC assessment, and five reviewers. The WAT V2 was used to measure the level of alignment for four criteria: categorical concurrence, depth-of-knowledge DOK) consistency, range-of-knowledge, and balance of representation. The results of the study revealed that DOK level-1, 5(8.4%), level-2, 20(33.9%), level-3, 30(50.8%), and level-4, 4(6.9%) were assessed from the total standards described in curriculum of 8th-grade. Student Learning Outcomes (SLOs) 31(81.6%) were targeted in the test, and among them, 7(18.4%) SLOs were targeted more than once for developing test items. The assessment of vocabulary and grammar standards met all alignment criteria, while writing showed no alignment across any dimension, oral communication and reading were partially aligned, meeting categorical concurrence, and DOK levels consistency, with insufficient range and balance representation.  On the basis of the results of the study, it is recommended that assessment administration may focus on assessment framework for representative content through DOK levels criteria to support comprehensive language development.